2021
DOI: 10.1038/s41467-021-26154-6
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 vaccine breakthrough infections with the alpha variant are asymptomatic or mildly symptomatic among health care workers

Abstract: Vaccine breakthrough SARS-CoV-2 infection has been monitored in 3720 healthcare workers receiving 2 doses of BNT162b2. SARS-CoV-2 infection is detected in 33 subjects, with a 100-day cumulative incidence of 0.93%. Vaccine protection against acquisition of SARS-CoV-2 infection is 83% (95%CI: 58–93%) in the overall population and 93% (95%CI: 69-99%) in SARS-CoV-2-experienced subjects, when compared with a non-vaccinated control group from the same Institution, in which SARS-CoV-2 infection occurs in 20/346 subje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 23 publications
7
39
0
Order By: Relevance
“…In order to answer these questions, we compared the concentration of anti-RBD, anti-Trimeric Spike-specific and neutralizing antibodies of fully vaccinated HCWs infected 3 and 6 months after vaccination to the corresponding values of non-infected HCWs ( Figures 3 A–3C). We show, as already reported by others ( Rovida et al., 2021 ), that at the time of the first positive NPS, vaccine-induced immunity had not waned in HCWs experiencing breakthrough infection because specific and neutralizing antibodies and MBCs were not reduced in comparison to the control HCWs. In addition, the rapid increase of Trimeric-Spike IgG and anti-RBD serum antibodies and the equally fast expansion of specific MBCs and plasmablasts strongly supports the hypothesis that vaccine-induced memory ( Goel et al., 2021a ), triggered by the virus, responds with the effect of limiting the infection and preventing symptoms (in 25/33; 75.7%) and severe disease (in all; 100%) and shortening the time of viral clearance.…”
Section: Discussionsupporting
confidence: 88%
“…In order to answer these questions, we compared the concentration of anti-RBD, anti-Trimeric Spike-specific and neutralizing antibodies of fully vaccinated HCWs infected 3 and 6 months after vaccination to the corresponding values of non-infected HCWs ( Figures 3 A–3C). We show, as already reported by others ( Rovida et al., 2021 ), that at the time of the first positive NPS, vaccine-induced immunity had not waned in HCWs experiencing breakthrough infection because specific and neutralizing antibodies and MBCs were not reduced in comparison to the control HCWs. In addition, the rapid increase of Trimeric-Spike IgG and anti-RBD serum antibodies and the equally fast expansion of specific MBCs and plasmablasts strongly supports the hypothesis that vaccine-induced memory ( Goel et al., 2021a ), triggered by the virus, responds with the effect of limiting the infection and preventing symptoms (in 25/33; 75.7%) and severe disease (in all; 100%) and shortening the time of viral clearance.…”
Section: Discussionsupporting
confidence: 88%
“…A study done with 3720 Italian healthcare workers fully vaccinated with the BNT162b2 vaccine showed that the 100day cumulative incidence of vaccine breakthrough infections by the alpha variant was 0.93% in vaccinated vs. 5.78% in non-vaccinated individuals (170). Furthermore, antibody and Tcell responses are not reduced in subjects with breakthrough infection (170). Other studies have been characterized SARS-CoV-2 breakthrough infections in individuals fully vaccinated with mRNA vaccines (BNT162b2 and mRNA-1273).…”
Section: Viral Load In Vaccinated and Unvaccinated Individualsmentioning
confidence: 96%
“…In this setting, a “real life” study reported a vaccine protection against acquisition of SARS-CoV-2 infection reported of 83% in the overall population and of 93% SARS-CoV-2-experienced subjects [ 11 ]. Importantly, in our cohort, including seronegative patients, no cases of COVID-19 were documented.…”
Section: Discussionmentioning
confidence: 99%